Veno-venous ECMO during surgical repair of tracheal perforation: A case report - Antonacci, Filippo (Int J Surg Case Rep, 2017)
INTRODUCTION: Extracorporeal membrane oxygenation (ECMO) is used extensively in cardiothoracic surgery both for hemodynamic and respiratory support. It has proven to be a valuable tool to maintain adequate oxygenation during tracheal surgery. Airway lesion may be an indication for veno-venous ECMO both in case of conservative management and in case of surgical repair. Here we report the case of a patient with a iatrogenic tracheal injury, successfully operated with the support of veno-venous extracorporeal oxygenation. PRESENTATION OF CASE: A 39-year-old female underwent an elective laparoscopic adhesiolysis. At the end of the procedure, the patient had developed subcutaneous emphysema. A CT-scan showed mediastinal and subcutaneous emphysema and left pneumothorax with a laceration of the membranous portion of the middle third of the trachea. A left pleural drain was inserted and a bronchoscopy showed a 2-cm long tear of the membranous portion in the middle third of the trachea. Veno-venous ECMO was established and surgical repair of the tracheal lesion was performed. Post-operative recovery was uneventful and the patient was discharged on 8th postoperative day. DISCUSSION: The use of Veno-venous ECMO allowed a safe intubation with optimal oxygenation. A selective intubation with a small tube was performed to prevent further tracheal injury and allow an adequate surgical space for tracheal repair. CONCLUSION: The use of ECMO support represents a safe and effective way to manage patients with ITI when surgical repair with minimally invasive ventilation is needed. Since this is a case report larger studies are needed to validate the technique.